Successful application of vagus nerve stimulation in super refractory status epilepticus associated with MERRF syndrome - Leyla Baysal; Sabrina Jobi; Simone Zimmermann; Ann-Kristin Helmers; Nils Gerd Margraf (Epilepsy & Behavior Reports)
Myoclonic epilepsy with ragged red fibers (MERRF) syndrome is a rare mitochondrial disorder marked by myoclonus, ataxia, cognitive impairment, myopathy, and sensorineural hearing loss. Seizures in MERRF syndrome are often resistant to standard antiseizure medication. We present a unique case of an adult patient with MERRF syndrome, caused by the m.8344A > G point mutation, who developed super-refractory status epilepticus (SRSE), successfully managed by the initiation and rapid escalation of vagus nerve stimulation (VNS) therapy. Over a two-year follow-up period, the VNS therapy enabled a long-term control of generalized tonic-clonic seizures. A further status epilepticus has not yet occurred. VNS may therefore be a promising therapeutic option for managing SRSE in patients with mitochondrial epilepsy syndromes.